From the history of the State historical and architectural reserve «Ancient Kyiv» - Horkova, A.O. (Сіверщина в історії України, 2021)
The State Historical and Architectural Reserve «Ancient Kyiv» is unique in terms of intension in percentage terms of monuments in ordinary buildings, location, number of varieties of objects of cultural heritage, their chronological range, character, and value. As of 2020, there were about 400 cultural heritage sites within the 175 hectares of the protected area. Today, the history of the Reserve can be formally divided into several periods and, in the context of the developed periodization, based on regulatory documents and factual material, reveal important and significant events in its activities.